Fermentation of dromedary camel (Camelus dromedarius) milk by Enterococcus faecium, Streptococcus macedonicus as a potential alternative of fermented cow milk. (April 2018) - El Hatmi, Halima; Jrad, Zeineb; Oussaief, Olfa; Nasri, Waad; Sbissi, Imed; Khorchani, Touhami; Canabady-Rochelle, Laetitia L.S.
Abstract: Physicochemical and sensory properties of fermented dromedary milk (FDM) and cow milk (FCM) by Enterococcus faecium (W1) or Streptococcus macedonicus (W2), two potent acidifying strains isolated from spontaneous FDM, were assessed and compared. The acidity variation was more pronounced in FDM than in FCM, while FCM showed higher viscosity than that of FDM. Whatever the milk source, the fermentation by the W1-W2 combination resulted in more viscous and more acid milks than those fermented by a single strain. The fermentation process resulted in higher contents of saturated fatty acids and especially in FCM. Nineteen aroma compounds were identified and separated into 6 chemical classes, where ethanol, acetoin and diacetyl were the major. The acetic acid that was particularly identified in FDM could contribute to vinegar-like flavor. Although the FCM presented the highest score for overall acceptability; sensory evaluation showed that FDM was more appreciated for its color. Interestingly, the highest DPPH-scavenging activity was found in FDM fermented by W1 strain. Therefore, fermented milks and particularly dromedary product could be considered as a functional food with benefits for human health. Highlights: E. faecium (W1) and S. macedonicus (W2) were isolated from spontaneous fermented dromedary milk. The fermentation by the W1-W2 combination resulted in more viscous and acid milk than those fermented by a single strain. The fermentation process did not affect the beneficial fatty acids. Ethanol, acetoin and diacetyl were the major aroma compounds identified in fermented milks. The highest DPPH-scavenging activity was measured in dromedary milk fermented by W1 strain.